Cultivo celular in vitro: importância para a pesquisa biomédica e dimensão da problemática de autenticação de linhagens celulares - Migita, Natacha Azussa [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Experimental models composed by human and animal cell lines are simplified and informative, allowing them to be widely used for biomedical research. Most laboratories that use in vitro cultivated cells maintain a variation of cell lines stored and cultivated. Therefore, misidentification and cross-contamination events can happen during cell lines handling. This problem can generate a repertoire of dubious results and papers, which may prejudice biomedical research. Recently it was created the International Cell Line Authentication Committee (ICLAC), which aims to spread knowledge about cross-contamination and misidentification of in vitro cell lines. Despite of the efforts spent trying to aware scientific community about the importance of the correct identification of cells, the number of papers based on misidentified cell lines it´s still worrying, compromising the reliability of out coming results and conclusions regarding them. The present study aims to analyze and discuss the main advantages and limitations of eukaryote in vitro cell lines use, characterizing the cell lines authentication problems. Therefore, compilation and critical analyses of literature data was realized, aiming to improve the understanding about this subject. Based on information about 445 cell lines with issues published by ICLAC it´s clear that contamination in human cell lines represented 89,2 % of mentioned problems. HeLa cell line was the responsible for most contamination, especially in 92 normal tissue cell lines, representing 44,6% of the contamination. These results reinforce the importance of periodic maintenance of cell lines cultures by labs and implementation of authentication methods as polymorphic STRs, besides obtaining cell lines from reliable sources and cell banks

Linhagens de células humanas e animais são modelos experimentais simplificados e informativos para pesquisas com diferentes finalidades e amplamente utilizados na pesquisa biomédica. A maioria dos laboratórios que utilizam células cultivadas in vitro mantém diversas linhagens celulares estocadas e em cultivo. Por essa razão, erros de identificação e eventos de contaminação cruzada podem ocorrer durante as atividades laboratoriais. Recentemente foi estabelecido o Comitê Internacional de Autenticação Celular (ICLAC), dedicado a tornar mais difundida a questão de contaminação cruzada e identificação equivocada de linhagens cultivadas in vitro. Apesar dos esforços despendidos para conscientização da comunidade científica, ainda é significativo o número de trabalhos publicados baseados em linhagens celulares equivocadas, o que compromete a fidedignidade dos resultados obtidos e as conclusões que deles advém. O estudo visa analisar e discutir as principais vantagens e limitações do emprego de cultura de células eucariotas, caracterizando e dimensionando a problemática da autenticação das linhagens celulares. Para tanto, será realizada uma compilação de dados da literatura e análise crítica das informações disponíveis sobre o tema até o momento. Com base em informações sobre 445 linhagens celulares problemáticas publicadas pela ICLAC, nota-se que contaminações entre linhagens humanas representaram 89,2% dos problemas observados. Digno de atenção, foi a contaminação de 92 linhagens de tecido normal por 44,6% de HeLa. Esses resultados ratificam a importância da monitoração periódica de culturas celulares pelos laboratórios e a implementação de métodos de autenticação como de STRs polimórficos, além de obter linhagens celulares devidamente autenticadas de biorrepositórios ou de fontes confiáveis
Keywords: Celulas - Cultura e meios de cultura; Biologia molecular; Biomedicina; DNA datiloscopia; Molecular biology